2000
DOI: 10.3171/jns.2000.93.6.1041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MAPK inhibitors on cerebral vasospasm in a dog double hemorrhage model

Abstract: The present study is the first in which the effects of MAPK inhibitors on vasospasm have been investigated in vivo. The authors demonstrate that MAPK may play a role in vasospasm and that PD-98059 is a potential candidate for the treatment of cerebral vasospasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Many studies have shown involvement of the MAPK signaling pathway in cerebral ischemia (Beg et al, 2006;Henriksson et al, 2007;Tibbs et al, 2000). Interestingly, it is only ERK1/2 and not p38 or JNK that is active during the first 24 hours after experimental SAH, as shown with quantitative Western blot of the proteins in large cerebral arteries and microvessels within the brain tissue proper (Ansar and Edvinsson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown involvement of the MAPK signaling pathway in cerebral ischemia (Beg et al, 2006;Henriksson et al, 2007;Tibbs et al, 2000). Interestingly, it is only ERK1/2 and not p38 or JNK that is active during the first 24 hours after experimental SAH, as shown with quantitative Western blot of the proteins in large cerebral arteries and microvessels within the brain tissue proper (Ansar and Edvinsson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study demonstrated that the mitogen-activated protein kinase inhibitor, U0126, improved behavior in dogs, despite the presence of severe aVSP, although the spasm was only moderate (≈50%). 16 This is the reverse of the question at hand. It shows outcome can improve without affecting aVSP.…”
Section: S32 Strokementioning
confidence: 96%
“…7,8 We previously examined the effects of MAPK inhibitors such as PD-98059 and U-0126 on cerebral vasospasm in an animal experiment. 9 Although the MAPK inhibitors demonstrated inhibitory effects on cerebral vasospasm after SAH, the inhibitory effects were inadequate. Recently, several authors reported that directly injecting endothelin or heme oxygenase-1 antisense ODN into the subarachnoid space prevented cerebral vasospasm.…”
mentioning
confidence: 99%